Analysis of Organizational Performance through Employee Engagement: Green Behavior, Green Organizational Culture, Green Compensation and Rewards - Prasidi, Abi (Greenation International Journal of Tourism and Management, 2025)
The purpose of this literature research is to help hypotheses for future authors in determining research related to organizational performance. The research article on organizational performance analysis through employee engagement: green behavior, green organizational culture, green compensation, and reward is a scientific literature article in the scope of human resource management. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct literature reviews of previous studies that are relevant and have been published. The data used in this study are secondary data, which are sourced from academic online media such as Thomson Reuters Journals, Sage, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Springer, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Green Behavior affects Employee Engagement; 2) Green Organizational Culture affects Employee Engagement; 3) Green Compensation and Reward affects Employee Engagement; 4) Green Behavior affects Organizational Performance; 5) Green Organizational Culture affects Organizational Performance; 6) Green Compensation and Reward affects Organizational Performance; and 7) Employee Engagement affects Organizational Performance